Niches after cesarean section in a population seeking hysteroscopic sterilization. (July 2017) - van der Voet, Lucy (Lucet) F.; Limperg, Tobias; Veersema, Sebastiaan; Timmermans, Anne; Bij de Vaate, A.Marjolein J.; Brölmann, Hans A.M.; Huirne, Judith A.F.
Abstract: Objective: To study the prevalence of hysteroscopically evaluated disruptions of the integrity of the uterine wall ('niches') in women with and without a previous cesarean section. Study design: A prospective cohort study was performed in a teaching hospital in the Netherlands. Women seeking hysteroscopic sterilization were included. A hysteroscopic evaluation of the anterior wall of the uterus and cervix to identify the existence of disruptions (niches) was performed in a standard manner. Primary outcome was the presence of a uterine niche, defined as any visible defect, disruption, or concavity (gap) in the anterior wall. Secondary outcome was to develop a registration form of niche features for hysteroscopic evaluation. Results: In total, 713 women were included, 603 without and 110 with a previous cesarean section. In women with a previous cesarean Section 83 (75%) niches were observed using hysteroscopy. Anterior wall disruptions were not observed in women without a cesarean section. The following niche features were identified and incorporated in a registration form: polyps, cysts, myometrium defect, fibrotic tissue, (abnormal) vascular pattern, lateral branches, mucus production inside the defect, and bleeding. Conclusion: In a prospective cohort study among women undergoing hysteroscopic sterilization, a uterine niche could be detected by hysteroscopy in 75% of women with a previous cesarean section.